Over 4000 works of literature. (Sl : Nodtronics, 2000)
Contents: an interactive Cd-rom which contains over 4000 complete works by great authors from all over the world including Australia. There are novels, plays, poetry, short stories, sacred texts, essays, the complete King James Bible, plus much more.
Keywords: Literature; Literature -- interactive